SOSIALISASI BAHAYA SAMPAH ORGANIK DAN NON ORGANIK BAGI MANUSIA DAN LINGKUNGAN PADA SANTRI MA'HAD AL JAMI'AH IAIN AMBON - Laila Sahubauwa; Heni Mutmainnah; Nana Ronawan Rambe; Corneli Pary (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2022)
Plastic waste is a material that has a negative impact for our life in earth. This is due to several reasons including; plastic waste takes 1000 years to decompose completely, the destruction of plastic waste by burning cause an incomplete combustion process that can produce toxic gases that are harmful to health, scientists from SCIRO (Commonwealth Scientific and Industrial Research Organization) and Imperial College London said that 90% of seabirds have plastic in their stomachs and it is estimated that number will continue to increase to 99% in the 2050. The purpose of carrying out this Community Service activity is to provide an understanding of the dangers of organic and non-organic waste for living things and the environment, an understanding of management of organic and non-organic waste, and an understanding of a lifestyle that is minimal in waste. The method used in this activity is lectures with presentation slide media on the dangers of organic and non-organic waste for humans and the environment. The results of the socialization show that the students of Ma'had Al-Jamiah IAIN Ambon understand the dangers of organic and non-organic waste, how to manage organic and non-organic waste and understand a lifestyle that is zero waste.